2018
DOI: 10.1016/j.conbuildmat.2017.12.218
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the SO3 content of an Algerian Portland cement: Study on the effect of various amounts of gypsum on cement properties

Abstract: h i g h l i g h t s Gypsum is a cement setting regulator, it is also a cement hydration accelerator. The use of gypsum at the optimum content, improves several cement properties. Its use below or above the optimum, affects adversely the cement properties. The optimum gypsum content is not fixed at 5%, it varies from a cement to another. The optimum gypsum content depends mainly on: SO 3 %, C 3 A %, Alkali % and cement SSB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 30 publications
2
26
0
1
Order By: Relevance
“…However, as reported by Mohammed and Safiullah [33], and shown in Figure 1, it has been proven through testing that the maximum hydration degree (elapsed time of 72 h) and compressive strength (elapsed time of 48 h) are increased when SO3 content is approximately 3.0%-3.2%. To maximize early compressive strength and apply the findings to construction sites, the research team added gypsum to OPC clinker, increasing SO3 to 3.1% and improving fineness by 111.8% (400 cm 2 /g on 3400 cm 2 /g).…”
Section: Introductionsupporting
confidence: 55%
“…However, as reported by Mohammed and Safiullah [33], and shown in Figure 1, it has been proven through testing that the maximum hydration degree (elapsed time of 72 h) and compressive strength (elapsed time of 48 h) are increased when SO3 content is approximately 3.0%-3.2%. To maximize early compressive strength and apply the findings to construction sites, the research team added gypsum to OPC clinker, increasing SO3 to 3.1% and improving fineness by 111.8% (400 cm 2 /g on 3400 cm 2 /g).…”
Section: Introductionsupporting
confidence: 55%
“…This implies that the production of ettringite is increased by the supply of SO 3 , as with the high SO 3 content in LCDBA, at 47.1%. In addition, Mohammed and Safiullah [ 27 ] revealed that the amount of ettringite formation highly correlates with the amount of SO 3 .…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…Its common composition is mainly defined by clinker and calcium sulfate. Clinker is formed by mixing and firing limestone and clay in rotary kilns at temperatures up to 1450 °C, resulting mainly in the phases: i) alite (C 3 S): 50% to 70% by mass, which determines the initial hydration through setting time and the strength development by precipitation of C-S-H calcium silicate gel and portlandite [31]; ii) tricalcium aluminate (C 3 A): 7% to 11% by mass [41], extremely reactive phase that affects hydration kinetics at an early age and reacts according to the presence or absence of calcium sulfate and Ca(OH) 2 [42]; iii) belite (C 2 S): reacts after 7 to 10 days of the mixture with water [43]; and iv) calcium ferroaluminate (C 4 AF): 7% to 13% by mass [41], reacts slowly but without calcium sulfate can react 40% after 1 day of hydration [43]. In Figure 7: Schematic of length changes of self-leveling cementitious mortars with and without shrinkage compensation by fast set and expansion at air conditions up to 160 days (adapted from [24,25]).…”
Section: Raw Materials Of Ternary System Opc-cac-casomentioning
confidence: 99%
“…Recently, the geochemistry dissolution theory has also been considered by many authors as an evolution for the interpretation of Portland cement hydration; however, it is still not totally established [44,45]. The optimum amount of calcium sulfate ranges from 3% to 5% by mass [41,46,47]. Above this value, the setting time remains practically constant, causing overdosage of the material and strength decrease [41].…”
Section: Raw Materials Of Ternary System Opc-cac-casomentioning
confidence: 99%